Odpowiedzi

Najlepsza Odpowiedź!
2010-02-13T12:00:55+01:00
X²-x=7²-7=49-7=42
a²-3a+1=(-4)²+3×(-4)+1=16+(-12)+1=16-12+1=4+1=5
1+x(x+4)=1+x²+4x=1+(-11)²+4*(-11)=1+121-44=122-44=78
x-2y =1-2*(-1)=1-(-2)=1+2=3
2x²-y(x+1)=2x²-xy-y=2*(-2)²-(-2)*5-5=2*4-(-10)-5=8+10-5=18-5=13
(m+1)(n-2)=mn-2m+n-2=2*1-2*1+1=2-2+1=1
1 5 1
2010-02-13T12:16:56+01:00
X do potęgi 2-x =7 ²⁻⁷=7 ⁻⁵= (¹/₇)⁵=¹/₁₆₈₀₇
a do potęgi 2- 3a + 1=-4²⁻¹²=-4⁻¹⁰=-(¼)¹⁰=-¹/₁₀₄₈₅₇₆
1+x(x+4)= -10×(-7)=70
x-2y=1-1=0
2x do potęgi 2 - y(x +1)=2×(-2)²⁻⁵⁻¹=4⁻⁴=(¼)⁴=¹/₂₅₆
(m+1)(n-2)=(2+1)(1-2)=2-4+1-2=-3
1 1 1